Korelasi Pengaruh Media Sosial Tik Tok Terhadap Prestasi Belajar Mahasiswa Prodi Pendidikan Ips Semester V STKIP Al-Maksum Langkat - Nia Daniati; Eka Darliana; Sakura Alwina (Jurnal Berbasis Sosial, 2022)
Social media TikTok is a social network and music video platform with various music effects, stickers, and other 3-dimensional images and is about 15 seconds long. This tik-tok application provides unique and interesting special effects that can make users feel happy and tempted to always see it. Thus each user can not only see it once or twice. The background in this research is due to the fact that when students have a little free time while doing their assignments, they always see tik-tok social media until they are tempted and forget their lectures. The purpose of this study was to find out how much influence social media Tik Tok had on student achievement in Semester V of Social Sciences Education Study Program, STKIP Al-Maksum Langkat. The formulation of the problem in this study is to find out how much influence social media tik-tok has on student learning achievement in Semester V of Social Studies Education Study Program. The benefits of this research are that it can provide new knowledge about the positive and negative impacts of tik-tok social media and as a basis for further research. This study uses qualitative research with data collection tools in the form of documentation methods, questionnaires and observations conducted in the classroom and interviews conducted directly on the fifth semester students of Social Studies Education Study Program.